Chemistry for a Clean and Healthy Planet - Ramasami, Ponnadurai; Gupta Bhowon, Minu; Jhaumeer Laulloo, Sabina; Li Kam Wah, Henri (Springer International Publishing : Imprint: Springer, 2019)
These proceedings gather carefully selected, peer-reviewed contributions from the International Conference on Pure and Applied Chemistry (ICPAC 2018). The event, the latest installment in a biennial conference series, was held in July 2018 in Mauritius. The respective chapters in this unique collection reflect a wide range of fundamental and applied research in the chemical sciences and various interdisciplinary subjects. In addition to reviews, they highlight cutting-edge advances. .